Numerical investigation of segmental baffle design in shell and tube heat exchangers with varying inclination angles and spacing - A. M. Mohammadzadeh; Bahram Jafari; Khashayar Hosseinzadeh; E. Paikar (Scientific Reports)
Abstract This article explores the crucial function that Shell and Tube Heat Exchangers (STHE) play in a variety of industrial applications. This research uses a three-dimensional computational fluid dynamics (CFD) simulation to model turbulent fluid flow and evaluate the performance of different baffle angle configurations. The study evaluates performance indicators such as overall heat transfer coefficient (OHT), shell side heat transfer coefficient (HTC), pressure drop (PD), and PEC (Performance Evaluation Criteria), this study evaluates their effect on Segmental STHE performance. The findings indicate that the PD in the shell section rises by a range of 56.8–60.9% for baffles inclined 0° to 30°. Additionally, compared to the 0° inclined baffles, the 30° inclined baffles exhibit a greater OHT of 4.5–6%. The PEC values that are determined for each type of baffle are the most crucial aspect to take into account while selecting the optimal STHE. The 25° inclined baffles have been selected as the most advantageous baffles due to their improved performance, as seen by their different PEC values. In the subsequent stage of the study, researchers investigated how changing the quantity of superior baffles (inclined) affects the STHE’s efficiency. As the number of baffles was increased from 4 to 10, the OHT rose by 14.5–17% and the PD increased by 138.63–141.7%. This thorough simulation revealed that the STHE with the 8 inclined baffles had the highest PEC value and was therefore the most appropriate STHE.